Engine power generation and emission performance of syngas generated from low-density biomass. (15th September 2017) - Indrawan, Natarianto; Thapa, Sunil; Bhoi, Prakashbhai R.; Huhnke, Raymond L.; Kumar, Ajay
Highlights: Off-grid small generation was demonstrated using syngas fed to SI engine. Syngas and natural gas generated peak powers of 5 KW and 9 KW, respectively. NOx generated from syngas was lower than that from natural gas at high load. Hydrocarbon generated from syngas was lower than that from natural gas at high load. Abstract: The power production from renewable sources must increase to meet the growing demand of power across the globe on a sustainable basis. Unlike most of gasification works that use high density biomass (e.g. wood chips) to generate a high quality syngas, here we introduce a novel gasification system that can use underutilized low density biomass resources to produce power and electricity with high efficiency yet minimum set-up requirement and low emissions. Switchgrass, one of locally abundant and low density biomass, was used as the biomass feedstock. A unique pilot-scale patented gasifier with a cyclonic combustion chamber having a capacity of 60 kW was used. A commercial natural gas – based, spark-ignition (SI) engine with capacity of 10 kW was modified to measure and control air-fuel ratio and fed with the syngas produced directly from the gasifier. The engine load was regulated by an electric load bank to evaluate the engine operational characteristics. The natural gas was used as the reference feed to evaluate the engine and emissions performance. Gas composition and flowrate, output power, electrical efficiency, and exhaust emissions such as CO2, CO, NOx, SO2, and hydrocarbons were measured. Net electrical efficiency of 21.3% and specific fuel consumption (SFC) of 1.9 kg/kWh were achieved while producing 5 kW at the maximum load using syngas, while 22.7% of electrical efficiency and 0.3 kg/kWh of SFC were achieved using natural gas at the equivalent load. NOx and HC emission produced from the engine was significantly affected by the gas fed and the load applied. CO2 emission varied moderately yet significantly with the increasing load, while CO and SO2 emissions did not strongly influenced by the load variation. NOx emission was 21.5 ppm that complies with the California emission standard limit (25.9 ppm). The study results showed that with minimum set-up, the downdraft gasification system coupled with existing commercial natural gas-based spark-ignited (SI) engine can satisfactorily generate sustainable power supply with high efficiency and minimum emissions to support off-grid power application.